(untitled) (Revista Archai, 2019)
This article aims at criticizing Hanson’s theory of the Western way of war from what historians have identified as its main problems: the alleged continuity of Western warfare through centuries, starting with the ancient Greeks; and the so-called “Asian contrast” from its main implications. Hence, it is divided into three sections: 1) the presentation and merits of Hanson’s theory; 2) its classical bases, or the emphasis of Greek warfare on decisive battle as a “cultural choice”; 3) the criticism.